Pemetaan Wilayah Resiko Infeksi Virus African Swine Fever (ASF) Beserta Tindakan Pencegahan dan Pengendalian Penyebaran di Kecamatan Kota Kefamenanu, TTU - Agustina Viktoria Tae; Steffanie M.C. Noach; Anastasia Kadek Dety Lestari (Lembaga Penelitian dan Pengabdian pada Masyarakat, 2026)
African Swine Fever (ASF) is a highly contagious and fatal viral disease affecting pigs, and it has become a serious threat in East Nusa Tenggara Province, particularly in Timor Tengah Utara (TTU) Regency. The outbreak has resulted in high mortality rates among pigs and has directly affected the livelihoods of traditional farmers. Tubuhue Village in Kota Kefamenanu District is among the areas with the highest mortality rates due to ASF, a situation exacerbated by the high mobility of livestock and the region’s proximity to the Timor-Leste border. The main problems faced by the community include limited knowledge of ASF prevention and control, as well as the minimal implementation of biosecurity measures. The absence of easy-to-understand educational media and clear risk mapping further hinders effective mitigation efforts. These conditions threaten the sustainability of pig farming, which serves as the primary source of income for the local community. This community service program proposes solutions through risk mapping of ASF transmission and the development of an educational minibook containing practical guidelines for disease prevention and control. Continuous training and extension activities will also be conducted to enhance the community’s capacity to apply biosecurity measures consistently. This approach is expected to strengthen farmers’ preparedness and reduce the negative impacts of ASF on livestock populations and the local economy.